(untitled) (Periphērica: Revista de Historia Social, Cultural, y Literaria, 2023)
This paper examines the sketches of imperial Spanish life written by Antonio Luna, a Filipino chemist-turned-writer-turned-general. Collected in his 1891 book Impresiones, these sketches demonstrate Luna’s attempts to claim autonomy through the written word. At the same time, they reveal the limits of literature’s power in modernity for subjects of colonial power, as the same scenes that provide other writers with their greatest triumphs offer frustration to Luna. As Luna’s characters traverse the cityscapes of the metropolis, they find themselves caught in the same flows of commodities and consumption as the coffee, sugar, and tobacco that traversed the globe, from the colonies to Europe, and offer hints of how patterns of consumption helped produce literary value in modernity.